Técnicas para sincronização de sistemas caóticos fundamentadas na aplicação das teorias de controle robusto - Cláudio Dias Campos (2012)
This thesis is dedicated to the study of the synchronization of nonlinear Lur’e systems. The synchronization of Lur’e systems is investigated in a context of discrete time precise parameters subject, or not, to chaotic behaviors. A systematic design methodology is proposed through the steps of system identification, discretization and synchronization controller synthesis. Based on H-infinity Robust Control Techniques described in terms of linear matrix inequalities (LMIs), two approaches were developed to solve the the synchronization problem: the first approach is based on parameter dependent Lyapunov functions and applies to piecewise linear systems – Poliquadratic Approach; the second is a less restrictive than the first one and is based on fuzzy control techniques – Fuzzy Takagi-Sugeno Approach. The proposed design methodology will be applied to the benchmark problem of Secure Information Transmission via additive disturbance in chaotic oscillators. Experimental validations will be performed and presented considering the PCChua and PCChua-SPICE platforms. The PCChua-SPICE platform is based on analogue computer methods and its being proposed as a viable and flexible alternative to the physical PCChua platform.